2014
DOI: 10.21101/cejph.a3912
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Latex Allergy among Healthcare Workers in Izmir (Turkey)

Abstract: The purpose of this study was to determine prevalence of natural rubber latex (NRL) allergy among healthcare employees and identify sensitive individuals. A total of 1,115 healthcare workers (HCWs) employed in Izmir Tepecik Education and Research Hospital participated in the study. Information on age, gender, occupation, history of allergy, and complaints were collected through a questionnaire. Serum latex-specific IgE level was determined. Among HCWs enrolled in the study, prevalence of latex sensitization wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
4
19
1
2
Order By: Relevance
“…However, natural rubber latex contains fifteen proven allergenic proteins (Hev b1 to Hev b15), which can elicit a hypersensitive immune response in the latexresponsive population and may lead to death if severe (anaphylaxis). The outbreak of latex allergy in the late 1980s and 1990s among healthcare workers [4][5][6][7] has drawn great attention from biomedical researchers, clinicians, and occupation safety regulatory agencies, and thus far, millions of affected individuals have been identified. Data published in the early 21 st century have shown that approximately 10%-17% healthcare workers [8][9][10][11] and as much as 73% patients with spina bifida 8,11,12 ) have been diagnosed with latex allergy.…”
Section: Introductionmentioning
confidence: 99%
“…However, natural rubber latex contains fifteen proven allergenic proteins (Hev b1 to Hev b15), which can elicit a hypersensitive immune response in the latexresponsive population and may lead to death if severe (anaphylaxis). The outbreak of latex allergy in the late 1980s and 1990s among healthcare workers [4][5][6][7] has drawn great attention from biomedical researchers, clinicians, and occupation safety regulatory agencies, and thus far, millions of affected individuals have been identified. Data published in the early 21 st century have shown that approximately 10%-17% healthcare workers [8][9][10][11] and as much as 73% patients with spina bifida 8,11,12 ) have been diagnosed with latex allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our study revealed concentration changes during the work practice. A skin allergy is confirmed on about 15% and non-cutaneous allergy in about 4% of subjects, indicating that, apart from contact to the skin, the respiratory exposure plays an important role on the latex sensitization [5,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…UFPR 4(2): 83-86 Abr-jun/2017 85 apresenta alergia ao látex, à p-fenilenodiamina e ao tiuram mix. Assim, a maioria das reações ao látex provém da exposição aos produtos com o látex tratado com amônia 13,14 , em especial nos profissionais da área de saúde, que são o grupo mais afetado devido ao frequente uso de luvas de látex para a prevenção de doenças infecciosas transmissíveis desde 1980 [1][2][3] . Estima-se que a prevalência de alergia ao látex para este grupo seja de 9,7%, contrastando com 4,3% para a população em geral 4 .…”
Section: Discussão E Conclusãounclassified
“…Entre o grupo mais afetados estão os profissionais da área da saúde, principalmente aqueles com exposição contínua a luvas de látex e atópicos [1][2][3] . Estima-se que a prevalência de alergia ao látex para este grupo seja de 9,7%, contrastando com 4,3% para a população em geral 4 .…”
Section: Introductionunclassified